Media dan Teknologi Pembelajaran PPKn dalam Memenuhi Tujuan dan Fungsi Pendidikan Kewarganegaraan - Ardita Ardita; Sarhan Pratama; Raul Adlan Maulana; Ilham Hudi; Sri Wahyuni (Universitas Palangka Raya, 2024)
This research explores the role of media and technology in supporting Civic Education (Civics) in the digital era. The focus is on using effective methods of media and technology to enhance students' understanding of civic concepts. The research methodology involved a literature study to analyze diverse sources of information. The results show that the integration of media and technology in civic education can enrich students' learning experience and strengthen the understanding of civic values. However, the positive and negative impacts of technology in this context need to be considered to keep students focused on meaningful learning. Thus, educational media and technology can play an important role in improving students' civic skills through various applications and platforms, while requiring careful supervision and direction from educational institutions and educators.